Caprine milk fermentation enhances the antithrombotic properties of cheese polar lipids. (October 2019) - Lordan, Ronan; Walsh, Aaron; Crispie, Fiona; Finnegan, Laura; Demuru, Martina; Tsoupras, Alexandros; Cotter, Paul D.; Zabetakis, Ioannis
Graphical abstract: Highlights: In vitro antithrombotic properties of raw and pasteurised caprine milk and cheeses were assessed. Fermentation alters the fatty acid composition of polar lipids. Fermentation increases the antithrombotic properties of milk polar lipids. L. lactis may play a significant role in altering the antithrombotic properties of caprine cheese. Microbial genes associated with phospholipid biosynthesis were detected in the bioactive cheeses. Abstract: The effect of fermentation on the antithrombotic properties of polar lipids in raw and pasteurised caprine milk was assessed through the production of various cheeses using the same starter culture. The total lipids (TL), total neutral lipids (TNL), and total polar lipids (TPL) were extracted from each milk and cheese and the TPL fatty acid profiles were analysed by GC–MS. It was determined that fermentation influenced the polar lipid fatty acid composition. The milk and cheese polar lipids exhibited potent antithrombotic activities with IC50 values ranging from 79 to 226 µg against platelet-activating factor (PAF) induced platelet aggregation. Finally, shotgun metagenomics determined the species-level microbial composition and functional potential of each milk and cheese. Several microbe-encoded phospholipid biosynthetic genes were identified in the most antithrombotic cheeses. Lactococcus lactis and other microbial species may play a significant role in determining the antithrombotic properties and fatty acid composition of caprine cheese polar lipids.